The Relationship of Social Support and Spirituality to Resilience in Chronic Kidney Disease Patients Undergoing Regular Hemodialysis at Adam Malik Hospital Medan in 2025 - Agrivina, Dinaya; Nasution, Bayu Rusfandi; Nasution, Tetty Aman; Saragih, Rina Amalia Caromina (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2026)
BACKGROUND End Stage Renal Disease (ESRD) patients undergoing hemodialysis are faced with demanding long-term therapy that often has a psychological impact. Resilience, the ability to adapt and recover from difficult situations, is an important protective factor for patients to manage medication adherence. External factors such as social support and internal factors such as spirituality were identified as aspects associated with individual resilience. METHODS This research is an analytic study with a cross-sectional design. Data were obtained through distributing questionnaires at Adam Malik Hospital Medan in 2025. Data were processed using Statistical Package for the Social Science (SPSS) software. RESULTS Based on the results of the analysis of 50 research samples, it was found that respondents had a high (66%) and moderate (34%) distribution of resilience. Social support and spirituality have a significantly positive relationship with individual resilience levels. CONCLUSIONS The majority of PGTA patients undergoing HD at Adam Malik Hospital have high levels of resilience. Social support and spirituality play an important role in increasing individual resilience. Therefore, good social support and spirituality are necessary in order to support treatment compliance, adaptation, and quality of life for HD patients.